Analysis of Service Quality, Word of Mouth, and Hospital Image on Inpatient Satisfaction at X Jayapura Hospital - Thalia Gabriella Siriwa; Cokki Cokki (Journal of Business, Social and Technology, 2026)
Background: Postharvest deterioration of tropical fruits is strongly influenced by respiration activity, which is highly sensitive to storage temperature. However, limited information is available on respiration kinetics of underutilized fruits such as namnam (Cynometra cauliflora), hindering proper postharvest management strategies. Objective: This study aims to evaluate the effect of storage temperature on respiration kinetics and to estimate the preliminary shelf life of namnam fruit using kinetic modeling approaches. Method: Namnam fruits were stored at 10°C, 20°C, and 30°C and analyzed using a closed-system CO₂ absorption method with triplicate measurements. Respiration rates were calculated and further evaluated using linear regression, Arrhenius modeling, Q10 temperature coefficients, and a zero-order degradation model for shelf-life prediction. Result: Respiration rate increased with rising temperature, showing a strong linear relationship (R² = 0.9984). Arrhenius analysis produced an apparent activation energy of 27.3 kJ mol⁻¹ with a moderate model fit (R² = 0.6682). Q10 values ranged from 1.45 to 1.68, indicating moderate temperature sensitivity. Estimated shelf life decreased from 13.46 days at 10°C to 9.06 days at 20°C and 6.26 days at 30°C. Conclusion: Lower storage temperatures effectively reduced respiration activity and extended shelf life, although respiration-based predictions should be validated using direct quality and sensory parameters for practical application.